Experimental and numerical investigation on enhancing the structural integrity of composite sandwich structure. Issue 9 (July 2019) - Mostafa, A
Composite sandwich structure possesses unique characteristics in which the facings' material provides a high in-plane stiffness/strength, while the core material keeps the facings a part to enhance the flexural stiffness/strength. However, sandwich structure is susceptible to shear failure due to the weak bond between the facings and the core materials. This article addresses this issue and provides an efficient semi-circular shear keys concept to be inserted in the interfacial surface between the sandwich structural elements to improve the facings–core interaction with marginal sacrifice in the strength-to-weight ratio. Composite sandwich panels composed of glass fibre–reinforced polymer skins and polyurethane foam core material have been investigated in this study. Mechanical tension, compression and shear tests were performed on the facings, while compression tests were conducted on the core materials to define the elasto-plastic response of the constituent's materials. Four-point bending tests were performed on the conventional composite sandwich panel and panels incorporated with shear keys concept. Considerable improvement in the flexural stiffness and strength along with detouring the crack path was noticed for the samples incorporated with shear keys. A non-linear finite element analysis was established to verify the experimental results. Comparisons between the experimental and finite element results were presented and showed good agreement between both results which justified the parameters used in the finite element models and their capabilities to capture the mechanical behaviour and the damage mode of the investigated models.